Draft Annual Plan 1995 - 96 Andhra Pradesh Volume-II (Sectoral Programmes) 8. Social Services - Planning Commission (Planning Commission, 1995)
The Director of Medical Education is incharge of medical colleges, teaching hospitals, nursing college and schools and a dental college. The main function is to regulate teaching and training of undergraduates, post-graduates and super specialties, besides nursing education and maintenance of patient care in the teaching hospitals. The total bed strength of teaching hospitals is 12,112.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh